"I changed because I wanted to" - identity performance in Bharati Mukherjee?s selected works - Filipczak, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper focuses on the performance of cultural identities in Bharati Mukherjee`s "Jasmine" (1989), "Orbiting" (1988) and "Desirable Daughters" (2002). The paper argues that Mukherjee for the most part dismisses the notions of contingency and is inclined to the presentation of a voluntarist model of identity. Intentionality, choice and conscious transformation are perceived here as means for identity formation.
Keywords: South Asian American fiction; Mukherjee, Bharati (1940-2017); performance; agency; voluntarist model of identity